Interplay between SUMOylation and NEDDylation regulates RPL11 localization and function. Issue 1 (19th July 2018) - El Motiam, Ahmed; Vidal, Santiago; De La Cruz-Herrera, Carlos F.; Da Silva-Álvarez, Sabela; Baz-Martínez, Maite; Seoane, Rocío; Vidal, Anxo; Rodríguez, Manuel S.; Xirodimas, Dimitris P.; Carvalho, Ana Sofia; Beck, Hans Christian; Matthiesen, Rune; et al.
ABSTRACT: The ribosomal protein L11 (RPL11) integrates different types of stress into a p53‐mediated response. Here, we analyzed the impact of the ubiquitin‐like protein SUMO on the RPL11‐mouse double‐minute 2 homolog‐p53 signaling. We show that small ubiquitin‐related modifier (SUMO)1 and SUMO2 covalently modify RPL11. We find that SUMO negatively modulates the conjugation of the ubiquitin‐like protein neural precursor cell‐expressed developmentally downregulated 8 (NEDD8) to RPL11 and promotes the translocation of the RP outside of the nucleoli. Moreover, the SUMO‐conjugating enzyme, Ubc9, is required for RPL11‐mediated activation of p53. SUMOylation of RPL11 is triggered by ribosomal stress, as well as by alternate reading frame protein upregulation. Collectively, our data identify SUMO protein conjugation to RPL11 as a new regulator of the p53‐mediated cellular response to different types of stress and reveal a previously unknown SUMO‐NEDD8 interplay.—El Motiam, A., Vidal, S., de la Cruz‐Herrera, C. F., Da Silva‐Álvarez, S., Baz‐Martínez, M., Seoane, R., Vidal, A., Rodríguez, M. S., Xirodimas, D. P., Carvalho, A. S., Beck, H. C., Matthiesen, R., Collado, M., Rivas, C. Interplay between SUMOylation and NEDDylation regulates RPL11 localization and function. FASEB J. 33, 643–651 (2019). www.fasebj.org